Footwear chain and participation of micro and small enterprises in Tanzania: What are their coping strategies? - Kuzilwa, Joseph A.; Karia, Francis P. (Enterprenuership and Bussiness Development Research Cluster, 2026)
This book was sent to the DRPS for publication.